Epidemiological characterization of a nosocomial outbreak of extended spectrum β‐lactamase Escherichia coli ST‐131 confirms the clinical value of core genome multilocus sequence typing. Issue 12 (28th September 2017) - Woksepp, Hanna; Ryberg, Anna; Berglind, Linda; Schön, Thomas; Söderman, Jan
Abstract : Enhanced precision of epidemiological typing in clinically suspected nosocomial outbreaks is crucial. Our aim was to investigate whether single nucleotide polymorphism (SNP) analysis and core genome (cg) multilocus sequence typing (MLST) of whole genome sequencing (WGS) data would more reliably identify a nosocomial outbreak, compared to earlier molecular typing methods. Sixteen isolates from a nosocomial outbreak of ESBL E. coli ST‐131 in southeastern Sweden and three control strains were subjected to WGS. Sequences were explored by SNP analysis and cgMLST. cgMLST clearly differentiated between the outbreak isolates and the control isolates (>1400 differences). All clinically identified outbreak isolates showed close clustering (≥2 allele differences), except for two isolates (>50 allele differences). These data confirmed that the isolates with >50 differing genes did not belong to the nosocomial outbreak. The number of SNPs within the outbreak was ≤7, whereas the two discrepant isolates had >700 SNPs. Two of the ESBL E. coli ST‐131 isolates did not belong to the clinically identified outbreak. Our results illustrate the power of WGS in terms of resolution, which may avoid overestimation of patients belonging to outbreaks as judged from epidemiological data and previously employed molecular methods with lower discriminatory ability.